Predictors of maternal outcome in women on mechanical ventilation in an obstetric intensive care unit: an observational study - Soni, Tanu; Tiwari, Priyadarshini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Present study was designed to note the indications for and the complications and outcome of women on mechanical ventilation in our obstetric intensive care unit, and in addition to look for the applicability and correlation of Sequential Organ Failure Assessment (SOFA) scores for the prediction of outcome in these women. Methods: A prospective observational study was conducted in the obstetric intensive care unit of our teaching hospital which included all women requiring mechanical ventilation in the study period. The diagnosis of the woman on admission, the clinical course and outcome along with total maximum sequential organ failure assessment (SOFA) score and SOFA score for each system were noted. Women were divided into two groups, survivors and non-survivors. Student t test and chi square test were used for analysis. Results: The foremost indication for mechanical ventilation was hypertension in pregnancy namely eclampsia and pre-eclampsia, followed by obstetric hemorrhage and then by hepatic failure. Maternal mortality rose significantly as the number of days of mechanical ventilation increased (p value <0.05). The total SOFA score correlated highly significantly with the outcome (p<0.0001). Conclusions: In women with eclampsia and pre-eclampsia suffering from respiratory failure, survival is inversely correlated with the number of days of mechanical ventilation. The total SOFA score is highly predictive of the woman’s outcome and all individual organ system scores also significantly correlate with outcome except for the score of coagulation system.